1996
DOI: 10.1021/jp953653o
|View full text |Cite
|
Sign up to set email alerts
|

129Xe NMR Study of the Bed Resistance to Molecular Transport in Assemblages of Zeolite Crystallites

Abstract: The NMR spectroscopy of xenon sorbed in beds of ZSM-5 zeolite is used to study the rate of adsorption of benzene molecules from the gas phase, as well as the rate of the combined process of adsorption and desorption in a bed consisting of two types of crystallites, some being initially benzene-loaded, some not. The exchange rate is shown to depend dramatically on the crystallite arrangement. The magnitudes of the observed rate constants and line shifts are confirmed by calculations based on simple models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…17,18,20 In particular, the combination of 129 Xe NMR spectroscopy with 1 H magnetic resonance imaging (MRI) Hp-129 Xe NMR spectra with 30% xenon (from high-density xenon optical pumping) in 70% methane. The experimental setting is as described in Figures 1 and 3a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,20 In particular, the combination of 129 Xe NMR spectroscopy with 1 H magnetic resonance imaging (MRI) Hp-129 Xe NMR spectra with 30% xenon (from high-density xenon optical pumping) in 70% methane. The experimental setting is as described in Figures 1 and 3a.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] The value of 129 Xe NMR using thermally polarized (i.e., nonoptically pumped) xenon for intracrystalline hydrocarbon diffusion studies at low temperature in heterogeneous catalysts has been demonstrated extensively in the recent past. [17][18][19][20][21] The combustion process within the coil region of the NMR probe head (Figure 1) takes place on and above the surfaces of molecular sieve pellets (i.e., only partially dehydrated Na-X zeolite). Although catalytic activity of this material is not expected, the reaction may still be influenced by the zeolite surface in contact with the flame.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This spectroscopy has also been used to study molecular dynamics in liquid crystals 8 as well as in microporous media. 9 The use of optical pumping techniques for the production of hyperpolarised (HP) xenon allows for a drastic increase in the sensitivity of 129 Xe NMR. This great enhancement of the signal intensity opens the possibility of exploring the accessibility of the nanochannels and the distribution of organic molecules in functionalized ordered mesoporous silica materials.…”
mentioning
confidence: 99%
“…The significance of eq 5 is not new. The concept of long-range diffusion developed by Kärger , through the perspective of self-diffusion in a bed of microporous particles leads to an identical result. Ruckenstein, Anathan, and Youngquist also correctly identified the role of the adsorption constant K in their detailed analysis of an equivalent problem: the competing effects of macro- and micropore transport resistances on a bidisperse particle.…”
Section: Introductionmentioning
confidence: 98%